2003
DOI: 10.1021/ac034241b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atmospheric Ozone on Microarray Data Quality

Abstract: A data anomaly was observed that affected the uniformity and reproducibility of fluorescent signal across DNA microarrays. Results from experimental sets designed to identify potential causes (from microarray production to array scanning) indicated that the anomaly was linked to a batch process; further work allowed us to localize the effect to the posthybridization array stringency washes. Ozone levels were monitored and highly correlated with the batch effect. Controlled exposures of microarrays to ozone con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(132 citation statements)
references
References 4 publications
1
124
0
4
Order By: Relevance
“…To overcome these disadvantages, image analysis methods were developed [20,21]. Additionally, Fare et al described deteriorating effects of atmospheric ozone on microarray data quality [22]. The homogeneous signal distribution on APTES/PDC could also be a reason for the higher sensitivity for lower capture DNA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these disadvantages, image analysis methods were developed [20,21]. Additionally, Fare et al described deteriorating effects of atmospheric ozone on microarray data quality [22]. The homogeneous signal distribution on APTES/PDC could also be a reason for the higher sensitivity for lower capture DNA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Values <1 and >2 are considered poor. It has also been demonstrated that environmental ozone levels affect Cy5 signal intensities, thus reducing data quality [Fare et al, 2003]. To overcome this issue, a novel dye "Hyper5" was developed, which is more ozone stable and photo stable than Cy5 [Dar et al, 2008].…”
Section: Signal Intensity Ratiomentioning
confidence: 99%
“…On occasion, there was considerable variability between microarray experiments done at different locations, or done at the same location on different days of the year. Careful analysis of the environmental factors found that the dyes used in microarray analysis are differentially sensitive to ozone, with Cy5/Alexa647 affected by 5-10 parts per billion ozone, whereas Cy3/Alexa555 are not affected until ozone levels reach >100 parts per billion [58]. Introduction of air purifiers to reduce ozone levels has improved the consistency of microarray data.…”
Section: Discussionmentioning
confidence: 99%